Vibration health monitoring for tensegrity structures. (15th February 2017) - Ashwear, Nasseradeen; Eriksson, Anders
Abstract: Tensegrities are assembly structures, getting their equilibrium from the interaction between tension in cables and compression in bars. During their service life, slacking in their cables and nearness to buckling in their bars need to be monitored to avoid a sudden collapse. This paper discusses how to design the tensegrities to make them feasible for vibrational health monitoring methods. Four topics are discussed; suitable finite elements formulation, pre-measurements analysis to find the locations of excitation and sensors for the interesting modes, the effects from some environmental conditions, and the pre-understanding of the effects from different slacking scenarios. Abstract : Highlights: We suggest a finite element which is more effective in simulating for vibration health monitoring. We discussed the possibility of using the finite element to prepare for better measurements. A solution for the effect of the environmental temperature changes on the natural frequencies has been given. We showed that different slacking scenarios gave different effects on the natural frequency.